Evaluation of the Khorana, PROTECHT, and 5‐SNP scores for prediction of venous thromboembolism in patients with cancer. (6th September 2021) - Guman, Noori A. M.; van Geffen, Roos J.; Mulder, Frits I.; van Haaps, Thijs F.; Hovsepjan, Vahram; Labots, Mariette; Cirkel, Geert A.; Y. F. L. de Vos, Filip; ten Tije, Albert J.; Beerepoot, Laurens V.; Tjan‐Heijnen, Vivianne C. G.; van Laarhoven, Hanneke W. M.; et al.
Abstract: Background: The Khorana score is a validated tool to identify cancer patients at higher risk of venous thromboembolism (VTE). Objective: We compared its predictive performance to that of the clinical PROTECHT and the polygenic 5‐SNP scores in patients who participated in the Dutch CPCT‐02 study. Patients/methods: Data on VTE and its risk factors were retrospectively collected for 2729 patients with advanced stage solid tumors planned for systemic cancer treatment. Patients were followed for 6 months. Overall discriminatory performance of the scores was evaluated by time‐dependent c‐indices. The scores were additionally evaluated dichotomously in competing risk models. Results: A total of 160 (5.9%) patients developed VTE during follow‐up. Time‐dependent c‐indices at 6 months for the Khorana, PROTECHT, and 5‐SNP scores were 0.57 (95% confidence interval [CI]: 0.55–0.60), 0.60 (95% CI: 0.57–0.62), and 0.54 (95% CI: 0.51–0.57), respectively. The dichotomous scores classified 9.6%, 16.8%, and 9.5% as high‐risk, respectively. VTE risk was about 2‐fold higher among high‐risk patients than low‐risk patients for the Khorana (subdistribution hazard ratio [SHR] 1.9, 95% CI: 1.3–3.0), PROTECHT (SHR 2.1, 95% CI: 1.5–3.0), and 5‐SNP scores (SHR 1.7, 95% CI: 1.03–2.8). The sensitivity at 6 months was 16.6% (95% CI: 10.5–22.7), 28.9% (95% CI: 21.5–36.3), and 14.9% (95% CI: 8.5‐21.2), respectively. Conclusions: Performance of the PROTECHT or 5‐SNP score was not superior to that of the Khorana score. The majority of cancer patients who developed VTE during 6‐month follow‐up were not identified by these scores. Future directions for studies on cancer‐associated VTE prediction may include combined clinical‐genetic scores.